Students’ Perception on Learning Grammar through Social Media during Covid-19 Pandemic - Winda Winda; titin suhartini kaaba; Harni Jusuf (Institut Agama Islam Negeri (IAIN) Manado, 2023)
This study aimed to describe students' perceptions in learning grammar using social media during the Covid-19 pandemic. This research used qualitative method with descriptive analysis. The subjects of this study were 20 students who had been taught grammar through social media due to the Covid-19 pandemic outbreak in the third semester of the English Education Department of the Sultan Amai State Islamic Institute of Gorontalo in the academic year 2020/2021 which were taken with a purpose. Data collection that used was questionnaires and interviews. The data obtained were analyzed through data reduction, data display, and drawing conclusions / data verification. The results of this study indicated that Students perception show that the most preferred social media for learning grammar by using social media was YouTube, Zoom, and WhatsApp and based on the result of research it showed that learning grammar by using social media are quite diverse and elaborate it. was very helpful, increasing the value, quite flexible but less motivated, less facilitated, not effective, has more disadvantages than advantages and less of interested. Based on students’ perception, 15 out of 20 students feel that they are not facilitated by the network to access the internet to learn grammar online because many students learn in their respective areas which are still difficult to signal to access the internet. Keywords: Grammar Learning, Social Media, Students’ Perception